From Planning to Implementation? The Role of Climate Change Adaptation Plans to Tackle Heat Stress. A Case Study of Berlin, Germany. - Mahlkow, Nicole; Donner, Julie (Sage Publications, 2020)
Global climate change increases the necessity for mid-latitude cities to tackle urban heat. Climate change adaptation plans are common policy mechanisms to approach the issue. This paper studies the city climate development plan (StEP Klima) of Berlin, Germany, by using Constellation Analysis. We analyzed to what extent StEP Klima might trigger planning and governance processes for the implementation of heat stress measures. Berlin’s plan brought attention to the local risks of urban heat and possible strategies. To translate its aims into decision makers’ everyday governance and planning practice, institutionalized guidance and an activation of policy instruments is needed.
Keywords: Großstadt; Hitzebelastung; Kommunaler Klimaschutz; Stadtentwicklungsplan; Kommunalplanung; Urban Governance; Konstellationsanalyse